Appreciating Functional Programming: A Beginner’s Tutorial to HASKELL Illustrated with Applications in Numerical Methods (Research Journal of Mathematics & Technology, 2022)
This paper introduces functional programming to the numerical methods community with theaim of popularizing this programming paradigm through a deeper appreciation for function as amathematical concept and, at the same time, for its practical benefits. The functional languageHASKELL is chosen amongst several choices because of its lazy evaluation strategy and high-performance compiler WinGHCi. We demonstrate the elegance and versatility of HASKELL bycoding HASKELL programs to implement well-known numerical methods.